Guide signs for approach roads to UMP - Tan, Boon Kei (2010)
This study intended to examine guide sign to UMP by inventory survey and questionnaire survey method. Throughout the whole site inventory survey, it was found that there was numerous of signage leading to UMP that were not following the standard of Arahan Teknik Jalan of JKR. This project intended to check JKR requirements whiôh include the distance from edge junction, visibility, availability, height of the guide sign and so on. Mostly criteria can be achieved by visibility survey. Questionnaire survey was also conducted as to gain drivers perception particularly new corners, to UMP. With all required data in hands, proper recommendation were made as guide for authorities like JKR when upgrading signage for approach roads to UMP in Gambang.